Clinical Characteristics of Clonorchis sinensis-Associated Cholangiocarcinoma: A Large-Scale, Single-Center Study - Chang, Jong-In; Lee, Keol; Kim, Dongwuk; Yang, Ju-II; Park, Jae Keun; Choi, Kyu; Kang, Soo Hoon; Lee, Kwang Hyuck; Lee, Kyu Taek; Lee, Jong Kyun; Park, Seon Mee; Park, Joo Kyung (Frontiers in Medicine, 2021)
Background:Clonorchis sinensis (CS) infection is considered a group 1 carcinogen of cholangiocarcinoma (CCA). There were very few studies regarding clinical characteristics of CS-associated CCA (CACC). This study aimed to investigate clinical characteristics of patients with CCA with or without CS infection. Methods: A total of 367 patients diagnosed with CCA who underwent diagnostic tests for CS infection were enrolled. CS infection was defined as follows: at least one positive serum ELISA test, skin test, stool microscopy, or bile microscopy. Results: There were 95 (26%) patients with CS infections. The median follow-up duration was 14.9 months (range, 6.07–36.17). The following significant differences were noted among patients with CACC compared to non-CACC; diagnosis at younger age (median 62 years vs. 65 years, p = 0.018), higher male to female ratio (83.2 vs. 61.8%, p < 0.001), and residence in CS-endemic area (46.3 vs. 25.4%, p = 0.014). Univariate analysis of prognostic factors indicated that tumor location, curative resection, tumor stage, and laboratory tests including CA 19-9, CEA, and bilirubin were significantly associated with overall survival, but CS infection was not. In multivariate analysis, tumor location, CEA, curative resection and tumor stage were identified as independent prognostic factors. Among patients under age 64, CACC group had lower survival rate than non-CACC group (p = 0.022). Conclusions: CACC had the following significant characteristics compared to non-CACC; diagnosis at younger age, higher male to female ratio, higher prevalence in CS endemic areas and poorer overall survival in patients under age 64.